Diagnóstico y actualización del Plan de Gestión Integral de Residuos Sólidos (PGIRS) en una empresa del sector químico de acuerdo a la norma NTC ISO 14001:2015 (2019)
The present monograph intends to diagnose and update the present System of Environmental Management (SEM) according to what is set on the 14001:2015 NTC ISO of a company of the chemical sector. It starts with the diagnosis of activities such as observation and description, and with the evaluation of the solid residues generated by the company. The procedure of diagnosis allows us to proceed to the execution of the project, which is made of a series of stages leading to the fulfillment of the objectives set out at the beginning.